Acupuncture of the adductor magnus for the treatment of post-stroke equinovarus: an investigation of the mechanism of action based on the anterior deep line - Yu, Bingxin; Teng, Xiuying; Lu, Lina (Frontiers in Neurology, 2025)
Post-stroke equinovarus foot is a prevalent motor dysfunction among stroke survivors. Its pathophysiology involves an imbalance of muscle tone, spasticity, and a subsequent disruption of the biomechanical chain resulting from central nerve injury. Conventional rehabilitation methodologies predominantly emphasize the restoration of localized muscular function, while interventions targeting motor pattern abnormalities resulting from systemic fascial conduction remain underdeveloped. In recent years, the fascial chain theory has provided significant anatomical and biomechanical perspectives for understanding the integrity and continuity of human movement. This paper proposes a novel integrative mechanistic framework, based on the fascial chain theory, in which needling the adductor magnus regulates the Deep Front Line (DFL) to improve the equinovarus foot posture. We hypothesize that the effects of acupuncture on the DFL of the vastus lateralis muscle are mediated through biomechanical and neuroplastic pathways: a mechanical pathway of fascial tension redistribution, a neuroplastic pathway of proprioceptive recalibration, and a resultant biomechanical pathway of gait optimization. While fascial chains are well-described anatomically, their therapeutic exploitation via acupuncture remains unexplored in the context of stroke rehabilitation. A thorough review of extant literature was conducted to demonstrate the scientific validity of this hypothesis across these three levels. This paper presents a novel perspective on the rehabilitation of equinovarus foot following a stroke and provides a foundation for future validation studies.